PEMANFAATAN DIGITAL MARKETING PADA PRODUK UMKM GHIDZA SASUKE DI KOTA GORONTALO - Siti Mayasari Pakaya; Muhammad Akram Mursalin; Abdul Wahab Thomas; Invabil Febrian (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a business sector consisting of enterprises that have a small to medium scale in terms of the number of employees, revenue, and assets. This study discusses the implementation of marketing mix strategies in Micro, Small, and Medium Enterprises (MSMEs) focusing on seven elements of the marketing mix: product, price, people, place, promotion, process, and physical evidence.Through the conducted survey, the researchers selected Ghidza Sasuke MSME, located in Gorontalo City, which operates in the processing of healthy food and snacks. The aim of this study is to reveal how MSMEs can optimize the application of these seven elements to enhance competitiveness and business growth. The findings of this study provide insights into the importance of adapting marketing mix strategies according to the characteristics and needs of the local market. The practical implications of this study can serve as a guide for MSMEs in developing effective marketing strategies to expand market share and increase profitability